COMPARATIVE STUDY OF ARTIONYMS IN ENGLISH AND UZBEK LANGUAGES (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the features of artionyms in English and Uzbek languages through a comparative study. It focuses on the origin, classification, semantic fields, and cultural significance of artionyms. The comparative analysis highlights both commonalities and differences in naming artworks, revealing how cultural values and historical developments influence linguistic choices. The study shows that artionyms not only serve as identifiers but also reflect deeper social and psychological meanings. Through examples from both languages, the research demonstrates the role of national mentality in the formation of artionyms.